A context-consent meta-framework for designing open (qualitative) data studies. Issue 3 (3rd July 2019) - Branney, Peter; Reid, Kate; Frost, Nollaig; Coan, Susan; Mathieson, Amy; Woolhouse, Maxine
ABSTRACT: To date, open science, particularly open data, in psychology has focused on quantitative research. This article aims to explore ethical and practical issues encountered by UK-based psychologists utilising open qualitative datasets. Semi-structured telephone interviews with eight qualitative psychologists were explored using a framework analysis. From the findings, we offer a context-consent meta-framework as a resource to help in the design of studies sharing their data and/or studies using open data. We recommend secondary studies conduct archaeologies of context and consent to examine if the data available are suitable for their research questions. This research is the first we know of in the study of "doing" (or not doing) open science, which could be repeated to develop a longitudinal picture or complemented with additional approaches, such as observational studies of how context and consent are negotiated in preregistered studies and open data.